(untitled) (Al-Qamar, 2020)
Apparent meanings of some Qur’ānic verses cause the delusion that the Quran contains contradictory information while there is no any contradiction in it. This delusion appears mainly because of lack of knowledge about the sciences needed to understand what these verses mean. For example, some verses seemed to mean that Allah never forgive disbelievers, polytheists, and apostates no matter how they ask His forgiveness during their lives in spite of the fact that some other verses emphasize that Allah may forgive all of them. Therefore, a beginner-level person with little knowledge of Arabic and Qur’ānic sciences might be under the delusion that these verses contain some contradictions. Commentaries of tafsīr scholars on these verses based on major principles of a Qur’anic science called mūhim-ul-ikhtilāfi wa al-tanāqudh refuted this alleged contradiction between these verses as I quoted some of them in this article.